Vaccine-induced immune thrombotic thrombocytopaenia – overview - Sleziak, Jakub; Gawor, Antoni; Gomułka, Krzysztof (Medical Studies/Studia Medyczne, 2022)
In response to the ongoing COVID-19 pandemic, pharmaceutical companies have been able to rapidly develop and distribute effective vaccines. Despite some common, minor, local, and systemic adverse effects following vaccination, there is also, in rare cases, a potential for the development of anti-platelet factor 4 antibodies, resulting in platelet activation and aggregation leading to potentially life-threatening thrombosis. Vaccine-induced immune thrombocytopaenia (VITT) is a rare immune response following administration of adenoviral vector vaccines against severe acute respiratory coronavirus 2 (SARS-CoV-2) such as ChAdOx1 nCoV-19 AstraZeneca – Oxford and Ad26.COV2. S Johnson & Johnson. Since the discovery of the syndrome, the mortality rate has decreased by 90%. Therefore, in this paper, data including epidemiology and pathophysiology of the syndrome, followed by the diagnosis criteria and management options, were collected. The authors believe that spreading knowledge further among primary care physicians and other healthcare professionals will lead to better VITT treatment outcomes.